Do Public Transfers Crowd Out Private Transfers to the Elderly? Evidence from Indonesia - Evi Yulia Purwanti; FX Sugiyanto; Akhmad Syakir Kurnia (Universitas Muhammadiyah Ponorogo, 2026)
This research explores the potential for government transfer programs to replace or ‘crowd out’ private assistance, with a particular focus on the significant rise in public transfers in Indonesia. Previous studies have not thoroughly examined the relationship between public transfers and the existing network of private transfers. This study adds to the empirical literature on intergenerational transfers by investigating the crowding-out effects between public and private transfers in Indonesia. This research draws on data from wave 5 of the Indonesian Family Life Survey (IFLS-5), with 2,240 selected samples of adult children and elderly parent pairs (dyads). Probit models and ordinary least squares were used to estimate and examine the robustness of the connection between private and public transfers. This study reveals that pension benefits reduce adult children’s propensity to transfer income to elderly parents. This finding reinforces the crowding-out effect hypothesis. Meanwhile, social assistance benefits lead to an increased likelihood of adult children transferring finances to elderly parents, creating a crowding-in effect on private transfers due to public transfers in the form of social assistance. The findings indicate that the needs and capabilities of both parents and children are crucial factors influencing the flow of intergenerational transfers.